The X-linked lymphoproliferative syndrome gene product SH2D1A associates with p62(dok) (Dok1) and activates NF-κB - Sylla, Bakary S. (The National Academy of Sciences, 2000)
The X-linked lymphoproliferative syndrome (XLP) is a genetic disorder in which affected males have a morbid or fatal response to Epstein–Barr virus infection. The XLP deficiency has been mapped to a gene encoding a 128-residue protein, SH2D1A, which is comprised principally of a Src homology 2 (SH2) domain. We now report that SH2D1A associates with Dok1, a protein that interacts with Ras-GAP, Csk, and Nck. An SH2D1A SH2 domain mutant that has been identified in XLP does not associate with Dok1, in accord with the hypothesis that this interaction is linked to XLP. The association of SH2D1A with Dok1 also depends on phosphorylation of Dok1 Y(449) in the sequence ALYSQVQK. Further, overexpression of SH2D1A is found to activate NF-κB in 293T cells. NF-κB activation by SH2D1A does not depend on the wild-type SH2 domain and is inhibited by a dominant-negative IκB kinase β. Thus, SH2D1A can affect multiple intracellular signaling pathways that are potentially important in the normal effective host response to Epstein–Barr virus infection.